Impact of SARS-CoV-2 Resistance to Antiviral Monoclonal Antibody Therapy on Neutralizing Antibody Response - Marc-Kendy Paul; Manish Choudhary; Amy Heaps; Rinki Deo; Daniela Moisi; Kelley Gordon; John Mellors; Carlee Moser; Paul Klekotka; Alan Landay; Judith Currier; Joseph Eron; et al. (Case Western Reserve University, 2024)
Background: Anti-SARS-CoV-2 monoclonal antibodies (mAbs) have played a key role as an antiviral against SARS-CoV-2, but there is a potential for resistance to develop. The interplay between host antibody responses and the development of monoclonal antibody (mAb) resistance is a critical area of investigation. In this study, we assessed host neutralizing antibody (nAb) responses against both ancestral virus and those with treatment-emergent E484K bamlanivimab resistance mutations. Methods: Study participants were enrolled in the ACTIV-2/Advancing Clinical Therapeutics Globally (ACTG) A5401 phase 2 randomized, placebo-controlled trial of bamlanivimab 700 mg mAb therapy (NCT04518410). Anterior nasal and nasopharyngeal swabs were collected for SARS-CoV-2 RNA testing and S gene next-generation sequencing to identify the E484K bamlanivimab resistance mutation. Serum nAb titers were assessed by pseudovirus neutralization assays.  Results: Higher baseline (pre-treatment) nAb titers against either ancestral or E484K virus was associated with lower baseline viral load. Participants with emerging resistance had low levels of nAb titers against either ancestral or E484K nAb at the time of study entry. Participants with emergent E484K resistance developed significantly higher levels of E484K-specific nAb titers compared to mAb-treated individuals who did not develop resistance. All participants who developed the E484K mAb resistance mutation were eventually able to clear the virus.  Conclusion: Emerging drug resistance after SARS-CoV-2-specific mAb therapy led to a heightened host neutralizing antibody response to the mAb-resistant variant that was associated with eventual viral clearance. This demonstrates the interplay between the antiviral treatment-directed viral evolution and subsequent host immune response in viral clearance.